Letter from James B. Guthrie to James Curtis Booth, May 25, 1854 - Guthrie, James (1854)
James B. Guthrie (1792 - 1869), United States Secretary of the Treasury from 1853-1857, responds to James Curtis Booth's (1810-1888) reported errors in the printed version of his report and problems with two of the three Evans Safety Guards.
Keywords: Guthrie, James, 1792-1869; Booth, James Curtis, 1810-1888; United States. Department of the Treasury; United States Mint; Mint of the United States